The somatotopy of observed emotions. (August 2020) - Sel, Alejandra; Calvo-Merino, Beatriz; Tsakiris, Manos; Forster, Bettina
Abstract: The ability to experience others' emotional states is a key component in social interactions. Uniquely among sensorimotor regions, the somatosensory cortex (SCx) plays an especially important role in human emotion understanding. While distinct emotions are experienced in specific parts of the body, it remains unknown whether the SCx exhibits somatotopic activations to different emotional expressions. In the current study, we investigated if the affective response triggered by observing others' emotional face expressions leads to differential activations in SCx. Participants performed a visual facial emotion discrimination task while we measured changes in SCx topographic EEG activity by tactually stimulating two body-parts representative of the upper and lower limbs, the finger and the toe respectively. The results of the study showed an emotion specific response in the finger SCx when observing angry as opposed to sad emotional expressions, after controlling for carry-over effects of visual evoked activity. This dissociation to observed emotions was not present in toe somatosensory responses. Our results suggest that somatotopic activations of the SCx to discrete emotions might play a crucial role in understanding others' emotions.